EMERGENCE OF IDEOLOGICAL THREATЅ IN THE CONDITIONЅ OF GLOBALIZATION (Scientific journal of the Fergana State University, 2024)
This article scientifically analyzes the ideas about the manifestation of ideological threats in the context of globalization. The article also highlights the considerations that in today's conditions of globalization, the factor of modern ideological threat covers all spheres of political, economic, social, cultural and spiritual life.